2006
DOI: 10.1248/cpb.54.230
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Glycosides from the Underground Parts of Solanum sodomaeum

Abstract: Solanum sodomaeum L. is a solanaceous plant native to wide areas of the Libyan desert. In a previous paper, the antineoplastic activity of the mixture of glycoalkaloids extracted from the fruits of S. sodomaeum L. against Sarcoma 180 in mice was reported.1) The glycoalkaloids extracted from the fruits, leaves and stems of this plant were investigated using MS and HPLC analyses, and solamargine and solasonine were identified in all the plant materials.2) Furthermore, it was reported that a cream formulation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In Vivo single dose studies in mice with the lethal Sarcoma 180 cells have similarly shown that the LD 50 and ED 50 resulted in a TI of 3.3. Figure 5 shows the lethal toxicity in normal untreated mice of single i.p.…”
Section: Kill Cancer Cells Only and Not Normal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vivo single dose studies in mice with the lethal Sarcoma 180 cells have similarly shown that the LD 50 and ED 50 resulted in a TI of 3.3. Figure 5 shows the lethal toxicity in normal untreated mice of single i.p.…”
Section: Kill Cancer Cells Only and Not Normal Cellsmentioning
confidence: 99%
“…Ex Vivo studies have demonstrated that BEC is effecttive against a wide spectrum of human cancers and that BEC is, in a dose dependent manner, selectively killing cancer cells without harming normal cells [11][12][13][14][15][16]32,34,47,[49][50][51][52]. Figure 4 illustrates the specificity of BEC on cancer cells and lack of effect on normal cells.…”
Section: Kill Cancer Cells Only and Not Normal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we had reported on the antiproliferative activity of these eight steroidal glycosides against human promyelocytic leukemia (HL-60) cells. 5) As a continuation to this study, we now describe the isolation and structural elucidation of 5 new steroidal glycosides obtained from the MeOH extract of the stems of S. sodomaeum L., along with 12 known glycosides. In the process, the structure of one of these glycosides was corrected.…”
Section: Notesmentioning
confidence: 95%
“…On acidic hydrolysis, 1 afforded L-rhamnose, D-xylose, and D-glucose, which were confirmed by optical rotation using chiral detection in HPLC analysis. The 1 H-and 13 C-NMR data of the sugar moiety and of the C-1-C-11 of the aglycone moiety of 1 were superimposable on those of 14, 5) indicating that the sugar chain attached to the b-hydroxyl group at C-3 of aglycone was identical to the sugar chain of 14. The stereochemistry at C-16, C-17, and C-20 of aglycone was defined on the basis of the nuclear Overhauser and exchange spectroscopy (NOESY) spectrum, in which key nuclear Overhauser effects (NOEs) were observed between respective protons, as shown in Fig.…”
mentioning
confidence: 96%